Efektivitas Kepatuhan Protokol Kesehatan Covid-19 Pada Pekerja Sektor Informal Di Kota Makassar (Studi Kasus di Terminal Mallengkeri) - Abadi, Muh Yusri; Marzuki, Dian Saputra; Rahmadani, Suci; Fajrin, Muhammad Al (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2021)
ABSTRACT Facing the adaptation of new habits (IMR) towards a productive and safe society against COVID-19, the Minister of Health issued a Minister of Health Decree number HK.01.07 / MENKES / 382/2020 concerning Health Protocols. The target in this study is the availability of a Covid-19 Health Protocol Compliance Effectiveness Study for Informal sector workers at Mallengkeri Terminal. This research is a quantitative method with cross sectional design. The research was conducted at Mallengkeri Terminal. The population in this study were all Mallengkeri Terminal drivers with a total sample of 97 respondents using accidental sampling technique. The results showed that there were 88 respondents (90.7%) who were good and 9 respondents (9.3%) who were not good enough in the effectiveness of compliance with the COVID-19 health protocol. The statistical test results showed that the achievement of goals and results (p = 0.004), target group satisfaction (p = 0.357), maintenance systems (p = 0.236), action (p = 0.068), facilities (p = 0.288), and motivation ( p = 0.744). Based on the research results, it can be concluded that only the achievement of goals and outcomes variables have a significant relationship with the effectiveness of compliance with the COVID-19 health protocol, while the other variables have no relationship